Leitura : interpretação e nível cognitivo-valorativo - O´connell, Daniel Mateus (2007)
The objective of this research was to find out if there is a correlation between the stages of cognitive-appraisal development and text interpretation, according to the theoretical proposal of Kohlberg (1969). In order to fulfill this aim, some theoretic assumptions related to research tendencies in reading; to reading in the Brazilian context, as well as to the cognitive-appraisal aspects involved in reading performance were taken into account. The field of study for this action based research was an English language school. An informative questionnaire and an authentic English Biblical text followed by a post-reading test were used as means of research. In order to evaluate the data, the intellectual reflections on the post-reading test were examined by the collaborators taking into consideration the appraisal indexes established by Kohlberg (1969). The analyses manifested that different levels of appraisal development, such as pre-conventional, conventional and post-conventional were presented by the readers. This suggests that each reader appraises the reading in a different manner and depending on the situation these appraisals can even be contradictory. The results indicate that interpretation depends on the cognitive-appraisal level attained by the reader, as initially expected in the beginning. It was a surprise; however, to discover that interpretation does not depend on the age or experience of the reader. Therefore, it is impossible to establish precise levels of cognitive-appraisal development.